1989
DOI: 10.1111/j.1365-2389.1989.tb01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the saturated hydraulic conductivity of an alfisol

Abstract: Alfisols exhibit a high degree of spatial variability in their physical properties. As a result, it is difficult to use information on physical parameters measured at one location to model larger-scale hydrologic processes. In this study, the saturated hydraulic conductivity, K,, of an Alfisol was determined on 109 undisturbed monoliths using the falling-head permeameter method. The model developed by Arya & Paris (1981) was used to calculate the pore volume from sand and clay fractions. Scaling factors were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In reality, fitting a statistical functional relationship between K s and texture per se has proved very unsuccessful in many instances. For example, Puckett et al (1985) as well as Bonsu & Laryea (1989) reported a significant correlation between K s and sand or clay, but failed to establish any statistical functional relationship between them. Other researchers such as Aronovici (1946), Talsma & Flint (1958), Winneberger (1974), Gumbs (1974) and Varallyay (1974) have also reported significant correlations between texture and K s or permeability.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…In reality, fitting a statistical functional relationship between K s and texture per se has proved very unsuccessful in many instances. For example, Puckett et al (1985) as well as Bonsu & Laryea (1989) reported a significant correlation between K s and sand or clay, but failed to establish any statistical functional relationship between them. Other researchers such as Aronovici (1946), Talsma & Flint (1958), Winneberger (1974), Gumbs (1974) and Varallyay (1974) have also reported significant correlations between texture and K s or permeability.…”
Section: Resultsmentioning
confidence: 91%
“…To check further the efficacy of equation (3), some K s data obtained in an alfisol (Udic rhodustalf) at the ICRISAT Centre, Patancheru, India (Bonsu & Laryea, 1989) were compared with those calculated by equation (3). Only data for non-gravelly samples were used for the comparison, since the gravelly and stony samples gave erratic and inconsistent results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations